Tuning of the magnetostrictive properties of CoFe2O4 by Mn substitution for Co - Bhame, Shekhar D.; Joy, Pattayil Alias (Journal of Applied Physics, 2006)
Marked changes in the magnetostriction of CoFe2O4 in the substitution of Mn for Co has been observed. The magnetostriction parallel to the applied field direction decreases with increasing Mn content, whereas the magnetostriction perpendicular to the field showed a marked increase for 10% of the Mn substitution. The observed magnetostrictive properties are correlated with the magnetic properties. The results suggest the possibility of tuning the magnetostrictive properties of cobalt ferrite for various applications by proper substitution. (c) 2006 American Institute of Physics.

Template-assisted synthesis and characterization of passivated nickel nanoparticles - Gopalan, E. Veena; Malini, K. A.; Santhoshkumar, G.; Narayanan, T. N.; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Potential applications of nickel nanoparticles demand the synthesis of self-protected nickel nanoparticles by different synthesis techniques. A novel and simple technique for the synthesis of self-protected nickel nanoparticles is realized by the inter-matrix synthesis of nickel nanoparticles by cation exchange reduction in two types of resins. Two different polymer templates namely strongly acidic cation exchange resins and weakly acidic cation exchange resins provided with cation exchange sites which can anchor metal cations by the ion exchange process are used. The nickel ions which are held at the cation exchange sites by ion fixation can be subsequently reduced to metal nanoparticles by using sodium borohydride as the reducing agent. The composites are cycled repeating the loading reduction cycle involved in the synthesis procedure. X-Ray Diffraction, Scanning Electron Microscopy, Transmission Electron microscopy, Energy Dispersive Spectrum, and Inductively Coupled Plasma Analysis are effectively utilized to investigate the different structural characteristics of the nanocomposites. The hysteresis loop parameters namely saturation magnetization and coercivity are measured using Vibrating Sample Magnetometer. The thermomagnetization study is also conducted to evaluate the Curie temperature values of the composites. The effect of cycling on the structural and magnetic characteristics of the two composites are dealt in detail. A comparison between the different characteristics of the two nanocomposites is also provided.
Keywords: Nickel nanoparticles; Polymer-metal nanocomposites; Strongly acidic cation exchange resin; Stuctural and magnetic properties; Weakly acidic cation exchange resin

Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic